Intelligent multichannel signal processing for future audio reproduction systems - Brandenburg, Karlheinz; Schneider, Martin; Franck, Andreas; Kellermann, Walter; Brix, Sandra (AES International Conference 2013: Sound Field Control, 2013)
It is possible to improve audio reproduction, active noise reduction systems, and sound field control by using multi-loudspeaker systems. Distributed arrays of transducers with intelligent audio signal processing need sophisticated signal processing algorithms. The paper looks both at some of the psychoacoustic fundamentals of auditory illusion (still partly unsolved) and proposals to build solutions based on the combination of wave field synthesis (WFS) and wave domain adaptive filtering (WDAF). We include the sketch of application scenarios for future systems with a large number of loudspeakers. Copyright © (2013) by the Audio Engineering Societ